1987
DOI: 10.1111/j.1600-0447.1987.tb02784.x
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss, cortisol levels, and dexamethasone suppression in major depressive disorder

Abstract: Appetite and/or weight loss are integral, albeit not necessary, symptoms of depression. We explored the contribution of diminished appetite and/or weight loss ascertained by history to the hypothalamic-pituitary-adrenocortical (HPA) axis dysregulation in 120 patients with primary major depressive disorder. Significant positive relationship for both appetite and weight loss with cortisol levels in plasma and cerebrospinal fluid (CSF) were observed. Plasma cortisol levels were consistently higher in patients who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 34 publications
0
9
0
1
Order By: Relevance
“…The dysregulation of endocrine feedback mechanisms in these patients will impact energy balance and disturb appetitive behaviour as well as sleep. Indeed, weight loss is frequently an integral symptom of the disorder ( Casper et al . 1987 ).…”
Section: Resultsmentioning
confidence: 99%
“…The dysregulation of endocrine feedback mechanisms in these patients will impact energy balance and disturb appetitive behaviour as well as sleep. Indeed, weight loss is frequently an integral symptom of the disorder ( Casper et al . 1987 ).…”
Section: Resultsmentioning
confidence: 99%
“…Also, in women with clinically significant levels of depressive symptoms at 5 and 9 months postpartum, higher depressive symptoms at 5 months were associated with less infant weight gain from 5 to 9 months (Gress-Smith et al, 2012). The loss in weight and/or appetite has been suggested to affect HPA-axis function, with weight loss associating with higher plasma cortisol levels (Casper et al, 1987). In the present study, we did not find any correlation between concentrations of FCMs and weight gain, indicating that the difference in weight gain observed in high and low LG groups is not associated with changes in HPA-axis function.…”
Section: Discussionmentioning
confidence: 99%
“…an activation of the HPA axis, which accompanied clinical improvement of non-melancholic depressed patients (Holsboer-Trachsler et al, 2001). Furthermore, reduced sleep (Antonijevic et al, 2000) and loss of appetite and weight (Casper et al, 1987), vegetative characteristics of severe melancholic depression, are closely related to HPA axis overactivity, whereas hypersomnia and increased appetite are related to hypocortisolism (Casper et al, 1988). Therefore, it has been suggested that the HPA axis activating effect of HE might be related to its preferable efficacy in patients with RVS (see Murck, 2003).…”
Section: Discussionmentioning
confidence: 99%